Las actividades físicas recreativas y el sedentarismo en los niños de la unidad educativa Paltas de la ciudad de Catacocha - Lalangui Mala, Luis Miguel (2016)
The present research work entitled: The Physical recreational activities and sedentary lifestyle with children at Paltas Educational Unit of Catacocha city, has been made to determine what kind of activities are suitable for children to wake up interest in recreation and this way their sedentary lifestyle decrease. The literature review is written en the following variables: Recreational physical activities is conceptualized topics about physical activity, importance of AF, AF for school children, types, benefits AF, Consequences of physical inactivity, sport and its advantages as a recreational activity, individual and collective sport as recreation, the modes recreation and advantages, recreational games. Second the sedentary lifestyle; the materials used were bibliographic and desktop materials; the type of methodology research were qualitative and quantitative is being pre-experimental type, because it is worked with a select group, the methods used during the development of the present research work were the analytic-synthetic, inductive, deductive and playfulness, the techniques and instruments used were direct observation, bibliographic records, survey and plan activities; for the result obtained were considered the results for higher incidence rates for the respective discussion of the positive and negative situations, analyzed this discussion the conclusions obtained were that children at Paltas Educational Unit lack of recreational physical activity; as a recommendation it has been proposal an alternative for 10 weeks of work.